Retrospective analysis of post-exposure to human anti-rabies treatment in Botucatu, São Paulo State, Brazil - Ayres, Jairo Aparecido [UNESP]; Paiva, B. S. R.; Barraviera, Benedito [UNESP] (Universidade Estadual Paulista (Unesp), Centro de Estudos de Venenos e Animais Peçonhentos (CEVAP), 2010)
This analysis aimed to identify characteristics of accidents that would, probably, provoke rabies infection. A total of 14,409 survey questionnaires for surveillance of human rabies from the Brazilian Information System for Disease Notification (SINAN), from 2000 to 2005, were analyzed. Regarding demographics, it was observed that 7,377 (51.5%) of the victims were white, 4,458 (30.93%) were children and 8,008 (55.58%) were males. Urban cases were prevalent (88.10%) while dogs were the animals most frequently involved in accidents, in 11,700 cases (81.19%). Bites (84.35%) and scratches (19.15%) were the most prevalent exposure types, and occurred predominantly on victims' extremities (38.79%). The prophylactic measure taken in 6,179 cases comprised anti-rabies vaccine; of these victims, 421 (2.92%) showed systemic reactions while 693 (4.80%) reported no response. The importance of developing awareness in professionals that should correctly report post-exposure immunoprophylaxis cases is emphasized given the high number of individuals who receive this type of treatment annually.
Keywords: rabies; post-exposure prophylaxis; anti-rabies serotherapy